99 Structural optimization of anti-CEA-GITR-CAR to reduce tonic signaling and improve antigen-specific reactivity. (9th November 2020) - Amaishi, Yasunori; Okubo, Yu; Wang, Yizheng; Wang, Linan; Kato, Takuma; Okamoto, Sachiko; Shiku, Hiroshi; Mineno, Junichi
Abstract : Background: Adoptive immunotherapy using chimeric antigen receptor (CAR) is recently reported as one of the effective cancer therapy. Especially CAR-T cell therapy targeting CD19 antigen in B-cell tumors have shown impressive clinical results and CAR-T cell products targeting CD19 have already approved. However as the high relapse rate is still the problem and the clinical efficacy of CAR-T cell therapy for solid tumors is currently inadequate, further improvement of CAR design is required.It is known that the design of CAR construct affects the function of CAR-T cells. For example co-stimulatory domain such as CD28 and 4-1BB is used in the second generation CARs, CD28z-CAR-T cells show higher anti-tumor activity, whereas 4-1BBz-CAR-T cells demonstrate superior in vivo persistence. To enhance survival of T cells, several attempts had been made to optimize the signaling domains. Recently, we have developed the novel CARs incorporated GITR (glucocorticoid-induced tumor necrosis factor receptor family-related protein) intracellular domain for T cell survival prolongation and inhibition of regulatory T cells' suppressive activity. It is also reported that the antigen-nonspecific activation of CAR-T cells (tonic signaling) is influenced by the CAR design, and excessive T cell activation leads exhaustion of CAR-T cells. Previously, we have found that the design of CAR, not only single chain variable fragments (scFvs), affect the strength of tonic signaling. Thus, the optimization of CAR construct is essential to induce antigen-specific response with minimal non-specific activation, which results in maximal efficacy. Methods: We have optimized the structure of anti-CEA-GITR-CAR targeting CEA antigen expressing solid tumor such as gastric and pancreatic cancer. We have constructed several CARs with the different composition such as hinge region, transmembrane domain, and the order of VL/VH in scFV region, and compared the tonic signaling and antigen-specific activity in CAR-T cells. Results: The property of CAR-T cells was largely affected by the CAR constructs, especially the hinge region. The CAR-T cells with CD8α hinge showed strong tonic signaling, the CAR-T cells with short hinge-CAR lost antigen specificity, and elimination of hinge region lowered the CAR expression level and antigen reactivity. Furthermore, GITR-CAR-T cells showed higher proportion of CCR7+CD45RA+ cells and lower expression of exhaustion markers (PD1, Tim3, and LAG3) compared to CD28z-CAR-T cells. Conclusions: Our CEA-GITR-CAR with the optimized scFV design and CD28-hinge demonstrated improved antigen-specific response with reduced tonic signaling, potentially indicating that our novel CAR-T cells may show improved clinical efficacy on solid tumor.